Molecular identification of Bartonella spp. and Rickettsia felis in fox fleas, Chile - Millán, Javier Maximiliano (2023)
Seventy-five flea pools (one to ten fleas per pool) from 51 Andean foxes (Lycalopex culpaeus) and five South American grey foxes or chillas (Lycalopex griseus) from the Mediterranean region of Chile were analyzed for the presence of DNA of Bartonella spp. and Rickettsia spp. through quantitative real-time PCR for the nouG and gltA genes, respectively. Positive samples were further characterized by conventional PCR protocols, targeting gltA and ITS genes for Bartonella, and gltA, ompA, and ompB genes for Rickettsia. Bartonella was detected in 48 % of the Pulex irritans pools (B. rochalimae in three pools, B. berkhoffii in two pools, B. henselae in one pool), and 8 % of the Ctenocephalides felis felis pools (B. rochalimae, one pool). Rickettsia was confirmed in 11 % of P. irritans pools and 92 % of the Ct. felis pools. Characterization confirmed R. felis in all sequenced Rickettsia-positive pools. All Ct. canis pools were negative. A Ct. felis pool from a wild-found domestic ferret (Mustela putorius furo) also resulted positive for R. felis. Although opportunistic, this survey provides the first description of zoonotic pathogens naturally circulating in fleas parasitizing Chilean free-living carnivores.